Gaya pengurusan konflik dan ciri kepimpinan di kalangan pengawasan sekolah menengah kawasan Parlimen Tambun Tulang, Arau, Perlis - Ruslie, Jair (2009)
The purpose of this research is to observe the style of conflict management and leadership attributes among perfecfs in the Tambun Tulang Parlimentary Territory, Arau Perlis. The data was gathered from the board of prefects of 9 secondary schools which were chosen randomly. A total of 200 prefects were chosen whereby 30 prefecfs were selected from each school. The measuring instruments used were Thomas-Klimann Conflict Mode and to mesasure/evaluate the leadership attributes the researcher come up with a questionnaire based on a cluster autocratic, democratic and laissez-faire styled of leadership. However, it was adapted to the style of leadership which is oriented on duties (task oriented), based on relationship (relationship oriented) and passive. The data was processed using the SPSS 12 wheras the hypothesis was assessd with the usage of T-Test and One Way ANOVA. From the study of the hypothesis, the demography element or factors did not show any significant disparity towards the leadership qualities. However the element of position held had a reverse effect , it was significant toward leadership style. In the conflict management style, only gender and level of positins held showed a significant differences. Apart from that, results from the research showed the existence of significant relationship between prefects' leadership and conflict management style. On the whole and specifically leadership which is relationship oriented and task oriented has a significant relationship with all the five conflict management stylec. The researcher has its own implication on the schools concerned. The prefects or the students should be given continuous training programmes to upgrade this skill in managing conflicts. In the present environment 1 situations of discipline problem which of late have been increasing drasticaly, it is the time the role of prefects to be use completely. The programme which has been planned could be fully used by the board of prefects to improve their skills in managing interpersonal and intrapersonal conflict. Simultaneously it will upgrade the quality of their leadership. The result ot the research will only be reality when schools in this area take the follow up action/step. The action can then be replicated for further studies